2011
DOI: 10.1021/nn102301y
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling Magnetoresistance with Sign Inversion in Junctions Based on Iron Oxide Nanocrystal Superlattices

Abstract: Magnetic tunnel junctions sandwiching a superlattice thin film of iron oxide nanocrystals (NCs) have been investigated. The transport was found to be controlled by Coulomb blockade and single-electron tunneling, already at room temperature. A good correlation was identified to hold between the tunnel magnetoresistance (TMR), the expected magnetic properties of the NC arrays, the charging energies evaluated from current-voltage curves, and the temperature dependence of the junction resistance. Notably, for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 65 publications
0
31
0
Order By: Relevance
“…For most applications, the chemical stability of magnetic nanoparticles is crucial in order to prevent agglomeration, precipitation, or oxidation. Moreover, their surface functionalization is essential not only to make them stable against degradation, but also to convey additional properties that enable their specific activity towards target cells, such as tumor cells in order to address hyperthermia, towards biological ligands for the development of electrochemical sensors, and also towards pollutants for the uptake of contaminants from water, thus leading to the fabrication of various nanocomposites with applications in many technological fields [ 28 , 29 , 30 , 31 , 32 ]. The strategies developed for the protection of magnetic nanoparticles, their surface engineering, and their integration in functional structures and materials, can be divided into two major groups: surface coating with inorganic materials (silica shell [ 33 , 34 ], carbon [ 35 , 36 ], metals [ 37 ]) and coating with organic materials (surfactants, polymers [ 38 , 39 , 40 , 41 ]).…”
Section: Magnetic Nanoparticles: Synthesis and Functionalizationmentioning
confidence: 99%
“…For most applications, the chemical stability of magnetic nanoparticles is crucial in order to prevent agglomeration, precipitation, or oxidation. Moreover, their surface functionalization is essential not only to make them stable against degradation, but also to convey additional properties that enable their specific activity towards target cells, such as tumor cells in order to address hyperthermia, towards biological ligands for the development of electrochemical sensors, and also towards pollutants for the uptake of contaminants from water, thus leading to the fabrication of various nanocomposites with applications in many technological fields [ 28 , 29 , 30 , 31 , 32 ]. The strategies developed for the protection of magnetic nanoparticles, their surface engineering, and their integration in functional structures and materials, can be divided into two major groups: surface coating with inorganic materials (silica shell [ 33 , 34 ], carbon [ 35 , 36 ], metals [ 37 ]) and coating with organic materials (surfactants, polymers [ 38 , 39 , 40 , 41 ]).…”
Section: Magnetic Nanoparticles: Synthesis and Functionalizationmentioning
confidence: 99%
“…The use of magnetic nanoparticles or ferromagnetic leads with metal nanoparticles is stimulating a new field of research, often referred as nanospintronics, since the SET characteristics exhibits even more interesting and potential phenomena with magnetic interactions due to the interplay between spin polarized and single electron tunnelling [122,123]. Magnetotransport through NPs has been investigated both in vertical structures within granular systems prepared by sputtering or physical evaporation methods [124,125] and within superlattices made of self-assembled colloidal NCs [126][127][128][129]. In 2000, Black et al reported spin-dependent electron transport in periodic arrays of cobalt nanocrystals with 10% magnetoresistance [130].…”
Section: Other Metallic Magnetic and Semiconducting Nanoparticlesmentioning
confidence: 99%
“…A guided procedure was used, driving the magnetically responsive NCs organized during slow solvent evaporation from corresponding colloidal solutions under the action of an external applied magnetic field. 60 GISAXS data were collected at a very small incidence angle (i = 0.05deg), as shown in Figure 12a. Indeed, the particular morphology of the sample allowed the measurement of the X-ray intensity scattered from 3D regions of the islands, even with the beam impinging at a highly grazing incidence angle on the substrate.…”
Section: Gisaxs -3d Self-assembly Of Iron Oxide Ncs 59mentioning
confidence: 99%